Analysis of partly interval-censored data under competing risks framework - Yosra, Yousif; Elfaki, Faiz Ahmed Mohamed; Hrairi, Meftah (2016)
Bayesian inference for partly interval-censored data is considered when there are two or more causes of failure with possibility of being masked. Cox proportional hazard model is adopted to estimate the regression coefficients. Simulation data show that the developed model is feasible and easy to implement.